Golden Moves: Developing a Transtheoretical Model-Based Social Marketing Intervention in an Elderly Population. (December 2013) - Dahl, Stephan; Eagle, Lynne; Ebrahimjee, Mustafa
Social marketing is increasingly being used by public and nonprofit organizations to deliver behavior change objectives. Drawing on the example of physical activity for the over 65s, we show how social marketing techniques can deliver a physical activity program for a priority group that has so far received little attention. In this study, conducted in the United Kingdom, we use a grounded theory approach to understand motivational factors and perceived barriers and to determine the types of messages and message channels that could be used for a potential social marketing–based intervention. We show how the findings of this pilot study can be used to develop such an intervention, and present a modeled intervention, based on the transtheoretical model of behavior change.